The dark side of cognitive illusions: When an illusory belief interferes with the acquisition of evidence‐based knowledge. (29th January 2015) - Yarritu, Ion; Matute, Helena; Luque, David
<x xml:space="preserve">Abstract</x> Cognitive illusions are often associated with mental health and well‐being. However, they are not without risk. This research shows they can interfere with the acquisition of evidence‐based knowledge. During the first phase of the experiment, one group of participants was induced to develop a strong illusion that a placebo medicine was effective to treat a fictitious disease, whereas another group was induced to develop a weak illusion. Then, in Phase 2, both groups observed fictitious patients who always took the bogus treatment simultaneously with a second treatment which was effective. Our results showed that the group who developed the strong illusion about the effectiveness of the bogus treatment during Phase 1 had more difficulties in learning during Phase 2 that the added treatment was effective.